2017
DOI: 10.21833/ijaas.2017.012.035
|View full text |Cite
|
Sign up to set email alerts
|

CO2-GDP NEXUS: Case for ASEAN 5

Abstract: This paper examines the causal relationship between carbon dioxide emission (CO2) and Gross Domestics Product (GDP). The nature of causality between CO2 per kilo tan (CO2) and GDP per capita were utilized using a cross country panel data from 1980 to 2010. The test was carried out using panel unit root tests, panel co-integration test, and panel vector error correction estimation and panel Granger causality tests to access the relationship between the respective variables. Our empirical results show the existe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…As in some previous studies of Choong (2009), Moudatsou and Kyrkilis (2011), Abdouli and Hammami (2017), Phuyal and Sunuwar (2018), Mustafa (2019), and Dinh et al (2019), FDI was utilized as a determinant of EG. The CO2 emissions and ED nexus is also studied in many prior studies likeAzam et al 2016, Saudi et al (2017), Balli et al (2019), Azam (2019) used CO2 emissions in their studies. The current study also utilized population growth in order to check its effect on EG in selected ASEAN countries.…”
Section: Theoretical Framework and Empirical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…As in some previous studies of Choong (2009), Moudatsou and Kyrkilis (2011), Abdouli and Hammami (2017), Phuyal and Sunuwar (2018), Mustafa (2019), and Dinh et al (2019), FDI was utilized as a determinant of EG. The CO2 emissions and ED nexus is also studied in many prior studies likeAzam et al 2016, Saudi et al (2017), Balli et al (2019), Azam (2019) used CO2 emissions in their studies. The current study also utilized population growth in order to check its effect on EG in selected ASEAN countries.…”
Section: Theoretical Framework and Empirical Modelmentioning
confidence: 99%
“…Almasaied et al (2008 observed a positive link among FDI and ED in five ASEAN countries. .On the other side, Saudi et al (2017) analyzed the nexus among ED and CO2 emissions and exposed positive nexus among them. Prior studies have analyzed the nexus among tourism, EG, FDI, and carbon emissions and found mixed evidence regarding their interrelationships.…”
Section: Introductionmentioning
confidence: 99%